2023
DOI: 10.1109/taes.2023.3289784
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic SAR Processing for High-Resolution Mapping Using Millimeter-Wave Radar Sensors

Abstract: In the field of autonomous driving, highly accurate representations of the environment are essential for trajectory planning as well as for estimating the vehicle's location. Today, this can be achieved with the help of chirp-sequence radar sensors or radar sensor networks. The possibilities for environmental mapping cover simple point clouds, target list based grid maps and raw data based high resolution synthetic aperture radar (SAR) maps. While for target list based grid maps it has already been shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Occupancy grid mapping is one of the most popular approaches for geographical mapping. Its usage is prominent in the domain of autonomous driving [14][15][16][17][18]. Mapping multiple sensors' information such as LiDAR, Radar and cameras to the surroundings of the vehicle in real time for the purpose of autonomous driving is a current topic.…”
Section: Probabilistic Occupancy Grid Mapping and Bayesian Fusionmentioning
confidence: 99%
“…Occupancy grid mapping is one of the most popular approaches for geographical mapping. Its usage is prominent in the domain of autonomous driving [14][15][16][17][18]. Mapping multiple sensors' information such as LiDAR, Radar and cameras to the surroundings of the vehicle in real time for the purpose of autonomous driving is a current topic.…”
Section: Probabilistic Occupancy Grid Mapping and Bayesian Fusionmentioning
confidence: 99%
“…With the help of SAR processing, a precise image of the environment with high dynamics can be created [23]. It was shown that not only highly reflective objects can be detected, but also the ground conditions can be mapped [24], [25]. The environment M to be mapped is rasterized into ๐ผ cells ๐‘š ๐‘– (๐‘–โ‰ค๐ผ).…”
Section: Sar Imagingmentioning
confidence: 99%